Circling a memory: a layered reflective method for generating subjective knowledge about childhood and teacher identity. Issue 3 (3rd May 2016) - Chang-Kredl, Sandra; Wilkie, Gala; Ghaznavi, Shahrzad
Abstract: This paper describes a memory and life story process engaged in by three former early childhood teachers. The reflective process was based in interpretative phenomenological analysis (IPA) and proceeded in a recursive and layered manner, circling around the participants' memory narratives. The aims of the study were: (1) to develop a critical approach to generating knowledge about childhood, and (2) to consider a teaching strategy for memory work in teacher education programs.